KEPASTIAN KEPEMILIKAN ATAS TANAH DI PEMUKIMAN ADAT YANG TERMASUK DALAM KAWASAN HUTAN ADAT PASCA PUTUSAN MK NOMOR 35/PUU-X/2012 JUNCTO PUTUSAN MENHUT NOMOR 941/MENHUT-II/2013 (STUDI DI DESA ALUR KEUJRUN KABUPATEN ACEH SELATAN) - ZUL AIDY (PREMISE LAW JURNAL, 2016)
The problem of land ownership status in adat settlement in Aceh has existed since the issuance of the Decree of the minister of Forestry and Plantation No.170/Kpts-II/2000 on June 19, 2000 which established forest and territorial waters of around 3,549,813 hectares. After the issuance of the Constitutional Court's Ruling No. 45/PUU-IX/2011 and 35/PUU-X/2012, all forest areas in Aceh as stipulated in the Decree of the Minister of Forestry has been declared void and, land ownership in adat settlement which used to be the State’s forest area has gotten its legal status. Land acquisition and ownership in adat settlement of forest area, according to the community at Alur Keujrun, South Aceh District, was a legal basis for land acquisition, based on border line right. Some measures which should be taken by them to get legal certainty on the land right is, principally, by controlling the land until they get recommendation letter from the village head which confirms that the requesting for the land right has been submitted to the Head of the Land Office. Some obstacles in getting legal certainty on the status of the land ownership in adat settlement of the State's forest area consist of inconsistency in the existence of land acquisition by the adat law community and communal right of disposal, non-synchronizing of legal provisions, and non- compliance with general principles and legal provisions. Keywords: Land Acquisition, Adat Forest, Adat Settlement